THE SIGNIFICANCE OF INFRASOUND IN THE HUMAN BODY: PHYSIOLOGICAL AND CLINICAL PERSPECTIVES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Infrasound refers to sound waves with frequencies below 20 Hz, which are generally inaudible to the human ear. Despite being imperceptible, infrasound has significant biological effects on the human body due to its ability to penetrate tissues and propagate over long distances. Both natural and artificial sources of infrasound contribute to human exposure. This article explores the physical properties of infrasound, its sources, physiological and pathological effects on human systems, and its potential clinical and environmental significance. Understanding the impact of infrasound is essential for public health, occupational safety, and future biomedical research.